The Relatıonship Between Functional Movement And Body Stability With Service Speed On Veteran Tennis Players - İpek Eroğlu Kolayiş; Hüseyin Günay (Türk Spor ve Egzersiz Dergisi)
The purpose of this study is to investigate the effect of functional mobility analyse and body stability on service performance among veteran tennis players. 25 veteran (senior) players (X̄age: 40.79±4.2) who are active licenced, have participated in the study voluntarily. The analyse of body stability of participant group has been done by using 4 core endurance tests; plank test (PT), lateral bridge test (LBTdom./non-dom.), flexor endurance test (FET) and extensor endurance test (EET). The evaluation of the participant’s mobility ability has been done with Functional Movement Screening test (FMS). Service performance scale has been conducted with Sports Radar Speed Gun SR3600. Participants have been asked for serving 8 times at maximal speed, the shots would be aimed at the cross service box with the dominant hand, accordingly with the tennis rules, balls which are hung to the net and out of service court (out) have been invalidated. Spearman Rank Order correlation analyse has been done on the gathered data by considering normality distribution at SPSS for windows 20.0 programme. In conclusion; a relationship couldn’t be found between the FMS and service performance speed rates of veteran (senior) tennis players. While it has been seen that there is a relationship between service performance speed and from the body stability core endurance tests; LBT (dominant), (p lt;0,05; r=0,550) FET (p lt;0,05; r=0,426) and EET (p lt;0,05; r=0,460), a relationship between PT and LBT(non-dom.) and service performance and between FMS and body stability core endurance tests hasn’t been encountered. A healthy psychical structure with a wide range of mobility can contribute to the performance of a variety of sport branches including tennis. When the role of service performance in a tennis match has been taken into account, it has been considered as one of the most important part of a play. For the studies that can be done in the future, with increasing the number of subjects, also using video analyse system can be recommended.